HUBUNGAN KINERJA PELAYANAN DENGAN PROFITABILITAS DI RSUD TONGAS KABUPATEN PROBOLINGGO - jurnalpps pps; Sri Syarif Fitriani (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
This study aims to find out whether there is a significant relationship between Service Performance and Profitability in the Tongas District Probolinggo Hospital in 2013 - 2017. The population used in this study is the Inpatient Census Report taken from indicators of Hospital Service Performance and Financial Statements of the Tongas District Hospital in Probolinggo in the form of Semester reports from 2013-2017.The results showed that there was no significant effect between the variables X, namely Service Performance where in this study using the BOR (Bed Occupancy Ratio) indicator, ALOS (Average Length of Stay), TOI (Turn Over Interval), BTO (Bed Turn Over) , GDR (Gross Death Rate) and NDR (Net Death Rate) for Y variables, namely ROA, NPM and ROE (Profitability). This is because the RSUD Tongas Probolinggo Regency is a regional public hospital not a private hospital where the number of patients treated and the number of patients treated the majority use health insurance cards, namely BPJS Kesehatan. The director must immediately take a policy to raise the type of hospital from type D to type C so that the claim rates for BPJS patients will rise and make changes to the applicable rates at the Hospital. By increasing the type of automatic hospital also to have an impact on the increase in income which will affect profitability.Keywords: BOR, ALOS, TOI, BTO, GDR and NDR and ROA, NPM and ROE.